Mundkur Memorial LectureCytology, Life Cycles and Spore Development in some Indian Rust Fungi (Urediniomycetes) - - PAYAK, M. M. (Indian Phytopathology, 2002)
The cytology, life cycles and spore development of some Indian rust fungi are described. Genera covered include Puccinia, Gymnosporangium and Uromyces.